Optimization of HPMC as Gelling Agent in Gel Formula of Etanol Extract of Bangun-Bangun Leaves (Plectranthus amboinicus (Lour) Spreng) - Suci Fitriani Sammulia; Aprilya Sri Rachmayanti; Joel Lam Parulian Tampubolon (Sean Institute, 2023)
Hidroxy Propyl Methyl Cellulose (HPMC) is a semi synthetic cellulose derivative gelling agent and can form a clear and neutral gel and has a stable viscosity in the long run. This study aims to determine the concentration of how much HPMC can form ethanol extracts of bangun-bangun leaves (Plectranthus amboinicus (Lour) Spreng) and stability of gel extract preparations. This research is an experimental study, in which the ethanol extract gel formulation of bangun-bangun leaves (Plectranthus amboinicus (Lour) Spreng) was conducted, by varying the concentration of HPMC at concentrations of 3%, 4% and 5%. Bangun-bangun leaves extract obtained from the maceration process and formulated in gel form. Furthermore, physical properties were evaluated, which included tests of adhesion, dispersion, pH, and viscosity on the bangun-bangun leaves extract gel. The evaluation results are then presented in tabular form. The evaluation results are then presented in tabular form. The optimum formula of the bangun-bangun leaves extract gel is a formula that contains 4% HPMC. Based on the results of the study is known that the results of the evaluation of the physical properties can be said to be stable after 4 weeks of stronge.